ANALISIS KUALITAS PELAYANAN DAN PROMOSI DALAM MENINGKATKAN KEPUTUSAN PEMBELIAN KOMODITI HANDPHONE PADA PT AKULAKU FINANCE INDONESIA (STUDI KASUS PADA GADGETMART BANJARMASIN) - M. Riffly Anugrah Saputra; Masrani Noor; Ni Nyoman Suarniki (Dinamika Ekonomi: Jurnal Ekonomi dan Bisnis, 2024)
This study aims to analyze the quality of service and promotion in increasing purchasing decisions for mobile phone commodities at PT Akulaku Finance Indonesia (Case Study at Gadgetmart Banjarmasin). This research method is a descriptive quantitative method. The population in this study were the community who provided services at PT Akulaku Finance Indonesia Banjarmasin from May 2023 to April 2024 totaling 240 people. This research is a case study at Gadgetmart Banjarmasin. The results of this study indicate that PT Akulaku Finance Indonesia in Banjarmasin strives to provide services that are as promised, reliable, accurate, and consistent. However, consumers still face obstacles to slow credit processes due to system and network disruptions. In terms of service dimensions, the company shows responsiveness by handling customer complaints quickly and responsively, and guaranteeing service through employee competence, politeness, and trust. In addition, the company also shows genuine concern for consumer needs and tries to understand their desires. Tangible dimensions, the advantages of physical facilities and good equipment support quality service to consumers. The performance of PT Akulaku Finance Indonesia Banjarmasin's promotional media is assessed from the effectiveness of delivering promotional messages to consumers. The company uses various promotional media such as billboards, banners, brochures, banners, digital ads, social media, and merchandise. Promotions are carried out according to the deadline and duration of the program that has been set. In terms of frequency, the company actively carries out promotions through various media with planned quantities to reach the target market.